Biodesulfurization of high sulfur coal from Shanxi: Optimization of the desulfurization parameters of three kinds of bacteria. Issue 18 (16th September 2020) - Xu, Jie; Liu, Xiangrong; Song, Changlei; Du, Zhipeng; Wang, Fangxin; Luo, Jingwen; Chen, Xinjuan; Zhou, Anning
ABSTRACT: This study mainly combines single factor experiment with orthogonal experiment to systematically investigate the effects of particle size, inoculum amount, pH value of the medium, ultrasonication time and species of surfactant on biodesulfurization of the high sulfur coal from Shanxi by using Thiobacillus ferrooxidans, Escherichia coli and Pseudomonas putida . The results revealed that the dominant strain was Pseudomonas putida which attained 58.23% of total sulfur removal during 10 days at the particle size of -125 + 75 μm, pH of 6.0, inoculum amount of 25 mL, ultrasonication time of 60 mins and Tween 80 concentration of 0.1%. Analysis of raw coal and biotreated coal by FTIR spectroscopy and X-ray diffraction indicated a modification of the coal structure after biodesulfurization. The curves of thermogravimetry (TG) for raw coal and biotreated coal also showed that the temperature of the coal pyrolysis significantly reduced, which meant that the thermal stability of the coal after biodesulfurization was lowered than raw coal. And the energy value of coal was not affected in the biodesulfurization process. After treatment with Pseudomonas putida, its calorific value only increased from 6308 cal/g to 6326 cal/g. Liquid products after biodesulfurization were extracted with a series of organic solvents, and each extract was characterized by gas chromatography-mass spectrometry (GC/MS), indicating the presence of sulfur-containing organic compounds in the liquid phase product. Ultimately, following these characterization results, the desulfurization mechanisms of all three bacteria were derived.